Reclaiming Womanhood in Islam: A Psycho-Humanistic Interpretation of Sister Fillah, You’ll Never Be Alone by Kalis Mardiasih - Shobichah, Muthi’atus; Ja'far, Ja'far; Umar Muhammad Noor (Faculty of Ushuluddin and Philosophy, 2024)
Studies on women in Islam continue to evolve despite having long been a focus of academic attention. In hadith studies, there remains a tendency toward interpretations that demean women, contradicting the original spirit of Islam, which upholds the dignity and equality of the sexes. This article examines the narratives of Muslim women in the book Sister Fillah, You’ll Never Be Alone by Kalis Mardiasih using Erich Fromm’s psycho-humanistic theory. The focus of the study includes the identity, role, and status of women in the modern socio-religious context, including resistance to gender-biased religious interpretations. The method used is qualitative text analysis with Fromm’s theoretical approach to explore women’s existential needs in the form of autonomy, freedom, belonging, and understanding of their normative rights. The results of the study show that through education and self-awareness, women can rediscover their humanity, which has been obscured by the patriarchal system. This book emphasizes the importance of valuing women’s bodies, the right to education, and recognition of women’s existence as whole human beings. With this approach, this article contributes to strengthening the discourse on gender justice in Islam through a reflective and contextual humanistic lens.